Gerakan Perempuan Nahdlatul Ulama dalam Transformasi Pendidikan Politik - Roviana, Sri (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2014)
‘NU’ that is an Islamic organization in Indonesia is the largest organization in terms of quantity (number of followers). This can be seen from the followers. There is a amount of 56% of the population of the Islamic religion in Indonesia, or 88,7% of the total populations of Indonesia, or there is a amount of 237,7 millions of Indonesian people. The women’s movement of NU, Muslimat and Fatayat NU, are the largest Muslim organization in Indonesia. Education in Islamic Boarding School (pesantren) as, reading ‘Kitab Kuning’ with teaching methods of ‘sorogan’ and ‘bandongan’ are often held in NU pesantren. Fatayat and Muslimat have been being active in the Indonesian political movements since Indonesian independence. This study is the explanation of their social movements which have been being done by them in several countries. Their particular social movements that have been done, are religious movements.